1985
DOI: 10.1002/eji.1830150822
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide‐linked surface molecules of monoclonal antigen‐specific suppressor T cells: evidence for T cell receptor structures

Abstract: By two-dimensional polyacrylamide gel electrophoresis analysis under nonreducing/reducing conditions, five proteins with interchain disulfide bridges are revealed on the surface of the suppressor T cell lymphoma line LH8-105 obtained by radiation leukemia virus-induced transformation of hen egg-white lysozyme-specific suppressor T lymphocytes. Two disulfide-linked surface proteins expressed by LH8-105 cells have been positively identified by immunoprecipitation with specific antisera. The major labeled membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Suppression may be mediated by many diverse cell types (8)(9)(10)(11)25) and by a variety of soluble products (10,25,26 (27,28). In other cases heterodimeric polypeptides have not been identified (29,30 It is interesting to speculate that the receptor polypeptides have similar molecular masses to murine 'y-8 heterodimeric proteins (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Suppression may be mediated by many diverse cell types (8)(9)(10)(11)25) and by a variety of soluble products (10,25,26 (27,28). In other cases heterodimeric polypeptides have not been identified (29,30 It is interesting to speculate that the receptor polypeptides have similar molecular masses to murine 'y-8 heterodimeric proteins (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of the two cell lines was not limited to phenotype, but also concerned the fine antigen specificity and the immunological function of the cells and their soluble products (Adorini et al, , 1983aRicciardi-Castagnoli et al, 1981Sinigaglia et al, 1984). We also previously showed that disulfide-linked molecules of 42 kd were revealed by two-dimensional gel electrophoresis of radiolabeled LH8 cell surface proteins under non-reducing/reducing conditions (Ballinari et al, 1985). We also previously showed that disulfide-linked molecules of 42 kd were revealed by two-dimensional gel electrophoresis of radiolabeled LH8 cell surface proteins under non-reducing/reducing conditions (Ballinari et al, 1985).…”
Section: Gene Rearrangementmentioning
confidence: 92%
“…However, the subunit composition ofthe antigen receptor on suppressor T cells (Ts) remains to be solved; several investigators have reported discrepant results, demonstrating that some Ts lines and hybridomas express a-and p-chain genes, whereas some do not (5)(6)(7)(8)(9) despite having their Ts function. Thus, two points should be discussed in this regard.…”
mentioning
confidence: 99%